2015
DOI: 10.1093/hmg/ddv165
|View full text |Cite
|
Sign up to set email alerts
|

RAN translation at CGG repeats induces ubiquitin proteasome system impairment in models of fragile X-associated tremor ataxia syndrome

Abstract: Fragile X-associated tremor ataxia syndrome (FXTAS) is a neurodegenerative disorder caused by a CGG trinucleotide repeat expansion in the 5' UTR of the Fragile X gene, FMR1. FXTAS is thought to arise primarily from an RNA gain-of-function toxicity mechanism. However, recent studies demonstrate that the repeat also elicits production of a toxic polyglycine protein, FMRpolyG, via repeat-associated non-AUG (RAN)-initiated translation. Pathologically, FXTAS is characterized by ubiquitin-positive intranuclear neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 76 publications
4
81
1
Order By: Relevance
“…FMRpolyG accumulates in neuronal inclusions in FXTAS patient brains and disease models (Todd et al, 2013). CGG RAN translation is required for toxicity in Drosophila and impairs protein quality control pathways (Oh et al, 2015; Todd et al, 2013), with similar findings observed in other repeat expansion disorders (Mizielinska et al, 2014; Yamakawa et al, 2015; Zhang et al, 2015). …”
Section: Introductionsupporting
confidence: 71%
“…FMRpolyG accumulates in neuronal inclusions in FXTAS patient brains and disease models (Todd et al, 2013). CGG RAN translation is required for toxicity in Drosophila and impairs protein quality control pathways (Oh et al, 2015; Todd et al, 2013), with similar findings observed in other repeat expansion disorders (Mizielinska et al, 2014; Yamakawa et al, 2015; Zhang et al, 2015). …”
Section: Introductionsupporting
confidence: 71%
“…However, disruption of proteostasis may be a common mechanism of toxicity for many of these aberrant translation products. Consistent with this hypothesis, several RAN products from C9ORF72 (polyGly-Ala, -Gly-Pro, -Gly-Arg, and -Pro-Arg) and FMR1polyGly have been linked to proteasomal dysfunction (Gupta et al, 2017; Oh et al, 2015; Yamakawa et al, 2015; Zhang et al, 2014b). C9ORF72polyPro-Arg is also associated with impaired autophagy (Gupta et al, 2017).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 67%
“…Initiation within the 5’ UTR occurs in at least two reading frames in the absence of an AUG start codon: the GGC (+1) frame yields a polyglycine product (FMRpolyG), and the GCG (+2) frame yields a polyalanine product (FMRpolyA). FMRpolyG accumulates in ubiquitinated inclusions in patient tissue and cellular and animal disease models, is necessary to elicit toxicity in Drosophila models of disease, and induces proteasome perturbations in Drosophila and HeLa cells (Todd et al , 2013; Buijsen et al , 2014; Oh et al , 2015). In an inducible mouse model of FXTAS that expresses the FMR1 5'UTR with 90 CGG repeats, turning off transgene expression reverses the formation of neuronal FMRpolyG-positive inclusions and repeat-elicited behavioral deficits (Hukema et al ., 2015).…”
Section: Ran Translation Of Cgg Repeats In Fxtasmentioning
confidence: 99%